Upaya Kelompok Ektrimis Untuk Menunggangi Isu Palestina-Israel: Analisis Diskursus Terhadap Narasi Kelompok Pro-Khilafah - Nurhidayat (IQTIDA : Journal of Da'wah and Communication, 2023)
In Indonesia, as the country with the largest Muslim population in the world, there has also been a strong and massive reaction to what happened in Palestine. Ismail Fahmi, through his social network analysis on social media Twitter, found that the Palestinian-Israeli issue was in fact being ridden by pro-khilafah groups. This paper attempts to study pro-khilafah groups that are trying to ride on the Palestinian-Israeli issue. The approach adopted in this paper is qualitative by using the netnographic method. Netnography is the application of ethnography in cyber space to examine the culture and behavior that occur in computer-based activities. In the midst of this struggle for influence in the narrative of defense of Palestine, there is one small group which, if not observed closely, can freely raise a theme which is quite dangerous: the caliphate. This small group moves among other Palestinian support groups. The pro-khilafah narrative emphasizes elements of Islamic identity rather than humanitarian issues. He blatantly tried to draw a line of distinction between Judaism and Islam. From there, then the pro-khilafah activists entered into their ultimate goal, which is to promote the caliphate as a solution to the problems of the Palestinian people. The narratives built by the supporters of the caliphate are generally accompanied by the hashtags #khilafahsolusipalestina and #palestinaneedskhilafah. Widespread public support for Palestine is used by a few groups to smuggle their pro-caliphate agenda. This group, although small, has its audience, including women. The pro-khilafah promote war as an attraction for men who want action, and elements of the safety of Palestinian families, children and women for female audiences.